STUDI KERAGAMAN WARNA DAN MORFOMETRIK KUDA SANDELWOOD DI KABUPATEN SUMBA TENGAH - Andreas Umbu Jara Sipul; Maxs U. E. Sanam; Budhy Jasa Widyananta (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
The sandalwood horse is an important part of Sumba culture and tradition which has a high social and economic value. Sandalwood horses have their own characteristics, so they need to have their own standardization. The purpose of this study was to determine the dominance of sandalwood horse color and the distribution of facial marking, leg marking, body marking and morphometric images of sandalwood horses. Sampling using purposive sampling method with a sample size of 102 sandalwood horses. The results of this study indicate that the sandalwood horse has a color that is red or bay 22.56%, breath or chesnut 18.63%, black or black 14.71%, canusu or cremello 12.75%, dragem or brown 10.79%, rhyme or palomino 9.81%, monkey black or black. gray 4.91%, dawuk or gray 1.97%, albino; or 1.96% white, 0.98% white or skewbald stripes and 0.98% breath or roan stripes. facial marking dominated by star type 62.5% followed by star, strip, snip 12.5%, bald face 12.5% and snip 12.5%; leg marking was dominated by stockings 62.5% followed by half stocking 25% and pastern 12.5%; and body marking, there was a stamp on the cheek and shoulder location 49.1%, a stamp on the cheek and thigh location 29.41% and a single stamp on the horse's cheek location 21.56%. Morphometric data obtained from 63 Sandelwood horses, namely the average body weight of male horses 320.94 kg and female horses 286.76 kg. The average height of a mare is 124 cm and a male horse is 115 cm. The average body length of male horses is 107.26 cm and female horses are 116.82 cm. The average chest circumference of a male horse is 140.47 cm and that of a female horse is 159.21 cm.